2019
DOI: 10.3390/ijms20194857
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Leaf Variegation in Pittosporum tobira under Low Temperature: Insights into the Physio-Biochemical and Molecular Mechanisms

Abstract: Leaf variegation has been demonstrated to have adaptive functions such as cold tolerance. Pittosporum tobira is an ornamental plant with natural leaf variegated cultivars grown in temperate regions. Herein, we investigated the role of leaf variegation in low temperature responses by comparing variegated “Variegatum” and non-variegated “Green Pittosporum” cultivars. We found that leaf variegation is associated with impaired chloroplast development in the yellow sector, reduced chlorophyll content, strong accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 95 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…The work of Shelef et al showed that white variegation of Silybum marianum could elevate leaf temperature during cold winter days [ 4 ]. Further study revealed that low temperature protective function of leaf variegation was partly associated with increased ROS-scavenging enzymatic activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Shelef et al showed that white variegation of Silybum marianum could elevate leaf temperature during cold winter days [ 4 ]. Further study revealed that low temperature protective function of leaf variegation was partly associated with increased ROS-scavenging enzymatic activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study identified differentially expressed genes involved in fatty acid elongation (ko00564) and glycerophospholipid metabolism (ko00062) (Figure 6B), which are crucial components of cell membranes. These metabolic processes could potentially enhance cell-membrane fluidity, serving as a mechanism for cell self-repair [39,40]. The damage caused by freezing stress to the leaves was significantly higher than the self-regulation capacity of foxtail millet leaves.…”
Section: Effects Of Freezing Stress On Membrane Injury Of Foxtail Mil...mentioning
confidence: 99%
“…Speci c primer pairs of 22 selected genes were designed using the Primer Premier 5.0 (Table 1). Data were presented as relative transcript level based on the 2 -∆∆Ct method [23].…”
Section: Validation Of Gene Expression Using Rt-qpcrmentioning
confidence: 99%
“…transcriptome sequencing with metabolomics has increased the power of bioinformatics analysis, and has been used to explore the important genes participating in the regulatory pathways of speci c metabolites and to elucidated the molecular mechanisms of melatonin's protective effects in plants [22,23]; Integration of transcriptome, degradome and smalls sequencing have provides a useful platform for some molecular mechanisms in plants [24]. However, their integration analysis is not used in R. glutinosa until now.…”
mentioning
confidence: 99%